Comparison of factors associated with the occurrence of menstruation-related symptoms in Japanese women without exercise habits and female soccer players: a cross-sectional study - Risa Mitsuhashi; Ryoko Mizushima; Hiroaki Natsui; Shuichi Machida; Yoshio Nakata (BMC Women's Health)
Abstract Purpose The aims of this study were to identify factors associated with menstruation-related symptoms and compare them between female soccer players and women without exercise habits. Methods This cross-sectional study was conducted between June and August 2022. Participants were healthy Japanese women aged 18–29 years, divided into two groups for comparison by exercise habits: women without exercise habits and female college soccer players. Participants responded to a self-administered questionnaire pertaining to their physical and menstrual characteristics, menstruation-related symptoms, and lifestyle habits. For menstruation-related symptoms, the Andersch and Milsom Scale was used to assess the severity of each of the 16 symptoms before and during menstruation. Lifestyle habits included stress, sleep, diet, and physical activity, which were assessed using Perceived Stress Scale, Japanese version of the Pittsburgh Sleep Quality Index, Food Frequency Questionnaire, and International Physical Activity Questionnaire, respectively. Data were analyzed using the t-test and multiple logistic regression analysis. All analyses were performed with a statistical significance of 5%. Results A total of 428 women (192 without exercise habits; 236 soccer players) participated in the study, and 244 women (99 without exercise habits; 125 soccer players) were analyzed. For women without exercise habits, long menstrual days (OR = 5.627; 95% CI, 1.046–30.259) and high levels of stress (1.082; 1.011–1.157) were factors before menstruation, and stress (1.131; 1.045–1.225) was a factor during menstruation were significantly associated with severe menstruation-related symptoms. Contrastingly, for soccer players, high body mass index (BMI) (1.460; 1.080–1.973), late bedtime (0.288; 0.110–0.753) before menstruation, older age (1.662; 1.073–2.575), high BMI (1.468; 1.089–1.980), family history of menstruation-related symptoms (3.090; 1.179–8.098), late bedtime (0.358; 0.133–0.958), caffeine consumption ( 0.359; 0.139–0.930), and less frequent breakfast intake (0.807; 0.653–0.997) were significant factors. Additionally, the factors associated with the occurrence of menstruation-related symptoms differed according to the symptom type. The most frequently associated factor in women without exercise habits was stress (13 symptoms). In female soccer players, the most frequently associated factor was BMI (8 symptoms). Conclusion Women presented different factors for menstruation-related symptoms depending on the presence or absence of exercise habits in their routine.